International relations. The global condition in the twenty-first century/ Frederic S. Pearson, J. Martín Rochester - Pearson, Frederic S. [et.al] (1997)
The study of international relatons, or getting a handle on the world, glimpse into the past, the historical development of the international system, A brid´s-eye view of the present, the contemporary, international system,explaining foreign policy behavior, why do natioonal-states do what thet do, the foreign plicy process, a view from the inside, playing the game of international relations, diplomacy before force, breakdown in the game, the resort to armed force, international law, myth or reality, international organizatons, links between goverments and between peoples, the control of violence, arms races and, arms control in the nuclear age,economic development, bridging the rich-poor gap, the management of resourcs, negotiacing the world´s troubled waters, land and air.